The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/su13042386
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Green Initiatives in the Manufacturing SME Sector in Poland

Abstract: Operating a business in the context of current environmental challenges requires managers to shift away from the management model focused solely on the achievement of economic goals. In this situation, pro-ecological (green) initiatives, in particular those that are innovative, are gaining significance. These measures allow for the mitigation and/or elimination of the environmental pollution while generating at the same time certain benefits for the companies implementing them, which is reflected in the improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 44 publications
(47 reference statements)
0
18
0
2
Order By: Relevance
“…In order to develop sustainable competitive edge, firms have to engage themselves in innovative and green initiatives (Wysocki, 2021). Many studies reported the existence of positive association between business performance and environmental concerns in relation to Martínez-del-Río, 2008;López-Gamero, Claver-Cortés, & Molina-Azorín, 2008).…”
Section: Green Competitive Advantagesmentioning
confidence: 99%
“…In order to develop sustainable competitive edge, firms have to engage themselves in innovative and green initiatives (Wysocki, 2021). Many studies reported the existence of positive association between business performance and environmental concerns in relation to Martínez-del-Río, 2008;López-Gamero, Claver-Cortés, & Molina-Azorín, 2008).…”
Section: Green Competitive Advantagesmentioning
confidence: 99%
“…In terms of job creation, no difference was found between SMEs with an innovation label and those that also with environmental indicators. Based on the results obtained in other studies, when innovation and environmental sensitivity and/or orientation are treated together, the results do not coincide [104,105,[110][111][112].…”
Section: Discussionmentioning
confidence: 72%
“…Sanchez-Medina et al [110] have investigated 168 Mexican small artisanal firms, and conclude that there is a positive relationship between eco-innovation and the three dimensions of sustainability, economic, social and environmental, adding that "the factors that best explain sustainability are: type of organization, product innovation and process innovation". Empirical research, conducted on a sample of 342 SME manufacturing companies operating in Poland, allows concluding that innovative green initiatives undertaken not only combine environmental objectives with economic ones, but also bring quantifiable benefits to the implementers in parallel to maintaining environmental safety [111]. These green innovations (save energy, prevent pollution or enable waste recycling) do not always translate into higher levels of financial performance.…”
Section: Innovation As a Driver Of Sustainabilitymentioning
confidence: 99%
“…MEC Koszalin currently has one coal-fired boiler adapted for co-firing biomass in the amount of 10% of the total fuel per year. However, in order to take advantage of the opportunities offered by this boiler, it is imperative that the bag filters are protected from damage first [110,111].…”
Section: First Pro-ecological Investment-modernization Of Boiler Wr 25 Nomentioning
confidence: 99%